Visit to Hilltop Home Site of Jan Pearson and Jackson Grote in Madera - Watkins, Howard::::::::: (1984)
Jackson Grote and Janice Pearson at picnic table with house trailer in back corner Sliced watermelon on table covered in red and white plastic tablecloth